Drama/Comedy - Guidance Associates (Australia : Contemporary Arts Media)
Comic drama draws on a lively reportoire of resources. This program discusses comedy; its plot devices, stock characters, different forms, satiric goals and black humor, and illustrates its diversity, with lively excerpts from Shakespeare, Kopit, Simon, friedman, Goldsmith and Shaw.
Title from container
Keywords: Comedy -- History and criticism; Drama -- History and criticism; Comedy